Multispectral optoacoustic tomography for the non-invasive identification of patients with severe anemia in vivo - Ganzleben, Ingo; Klett, Daniel; Hartz, Wiebke; Götzfried, Lisa; Vitali, Francesco; Neurath, Markus; Waldner, Maximilian (Photoacoustics, 2022)
The immediate diagnosis of severe anemia is crucial for patient outcome. However, reliable non-invasive point-of-care diagnostic tools for e.g., ICU monitoring are currently lacking. Using an advanced Multispectral Optoacoustic Tomography (MSOT) research device, we first substantiated a strong positive correlation of MSOT-signal and absolute hemoglobin concentration ex vivo in blood samples. In a clinical exploratory proof-of-concept study, we then evaluated 19 patients with different severities of anemia and controls by non-invasive in vivo measurement of hemoglobin in the radial artery. Our approach proved excellent in identifying patients with severe anemia triggering RBC transfusion based on a strong positive correlation of MSOT-signal intensity and hemoglobin concentration for 700 nm single wavelength and HbR unmixed MSOT-parameter analysis. In conclusion, our study lays the foundation to further develop MSOT-based real-time quantitative perfusion analyses in follow-up preclinical and clinical imaging studies and as a promising diagnostic tool to improve patient care in the future. DRKS00021442
CRIS-Team Scopus Importer:2022-10-28
Keywords: Anemia; Clinical study; Hemoglobin; Optoacoustic imaging